Interactive mirrOring Games wIth sOCial rObot (IOGIOCO): a pilot study on the use of intransitive gestures in a sample of Italian preschool children with autism spectrum disorder - Annunziata, Silvia; Santos, Laura; Caglio, Arianna; Geminiani, Alice; Brazzoli, Elena; Piazza, Elena; Olivieri, Ivana; Pedrocchi, Alessandra; Cavallini, Anna (Frontiers in Psychiatry, 2024)
Background: Autism Spectrum Disorder (ASD) is a neurodevelopmental disorder characterized by persistent deficits in social communication, social interaction, and restricted behaviors.The importance of early intervention has been widely demonstrated, and developmental trajectories in ASD emphasize the importance of nonverbal communication, such as intransitive gesture production, as a possible positive prognostic factor for language development.The use of technological tools in the therapy of individuals with ASD has also become increasingly important due to their higher engagement and responsiveness to technological objects, such as robots.We developed a training protocol using the humanoid robot NAO, called IOGIOCO (Interactive mirroring Games wIth sOCial rObot), based on the use of intransitive gestures embedded in naturalistic dialogues, stimulating a triadic interaction between child, robot and therapist.The training was divided into 6six levels,; the first 2 levels were called "familiarization levels"," and the other 4 were actually "training levels". The technological setup includes different levels of complexity, starting levels, from mirroring tasks to building spontaneous interactions. We tested the protocol on 10 preschool children with ASD (aged 2-6 years) for 14 weeks. We assessed them at recruitment (T0), at the end of training (T1), and after 6 months (T2).Results: We demonstrated the tolerability of the protocol. We found that one group (n=4), 2 males Sand 2 females) reached the training level, while another part group (n=6 males) remained at a familiarization level (mirroring).), and we analyzed the results for the two groups. In the group that reached the training grouplevels, we found promising results, such as an improvement in the Social Adaptive Domain of the ABAS-II questionnaire between T0 and T2.Conclusions: While current results will need a Randomized Controlled Trial to be confirmed, the present work sets an important milestone in the use ofusing social robots for ASD treatment, aimed at impacting social and communication skills in everyday life.